Hypertriglyceridemic subjects exhibit an accumulation of small dense chylomicron particles in the fasting state. Issue 1 (November 2015) - Irawati, Deasy; Mamo, John C.L.; Soares, Mario J.; Slivkoff-Clark, Karin M.; James, Anthony P.
Abstract Aim Normocholesterolemic subjects with elevated fasting plasma triglycerides are at increased risk of atherosclerosis through mechanisms that are not yet delineated. We hypothesized that elevated plasma triglyceride is associated with increased vascular exposure to pro-atherogenic lipoprotein remnants. To test this hypothesis, the abundance, and size distribution of chylomicron particles were determined in individuals with and without hypertriglyceridemia. Methods Twelve hypertriglyceridemic subjects (HTG group, triglyceride concentration ≥1.7 mmol/L) and twelve normotriglyceridemic subjects (NTG group) matched for age and gender were studied. The distribution of chylomicron particles was assessed by determining the fasting concentration of apo B-48 in serum lipoprotein fractions with Svedberg flotation rates of (Sf) > 400, Sf 20–400 and Sf < 20. Results The total concentration of apo B-48 in subjects with HTG was almost twice that observed in NTG controls with ∼80% of the increase residing in the Sf < 20 fraction (HTG: 8.7 ± 1.0 μg/mL vs NTG: 5.0 ± 0.6 μg/mL; P = 0.016). Significantly greater concentrations of apo B-48 were also observed in the less dense Sf 20–400 (HTG: 1.1 ± 0.2 μg/mL vs NTG: 0.4 ± 0.07 μg/mL; P < 0.001) and the Sf > 400 (HTG: 1.1 ± 0.3 μg/mL vs NTG: 0.3 ± 0.04 μg/mL; P < 0.001) fractions. An accumulation of triglyceride was also observed across all lipoprotein fractions in HTG subjects compared to NTG (Sf 400 & Sf 20–400: P < 0.001 and Sf < 20: P = 0.013). Conclusion Normocholesterolemic, moderately hypertriglyceridemic subjects are at increased atherogenic risk due to greater apo B-48 concentration in the small, dense lipoprotein fraction.